Humanizing delivery: a reality in a birth center? - Barros, Wilma Lilian Lima; Costa, Edileusa; Funghetto, Silvana Schwerz; Boeckmann, Lara Mabelle Milfont; dos Reis, Paula Elaine Diniz; Ponce de Leon, Casandra Genoveva Rosales Martins (Revista de Enfermagem UFPE on line, 2010)
ABSTRACT Objective: to know the women's perception in the postpartum about the provided health assistance during the labor and delivery at San Sebastian Birthing Center in District Federal, Brazil’s capital. Methodology: this is about a qualitative study, performed with ten women who experienced the delivery and postpartum period in this birthing center. The project was approved by the Ethics Committee of the Health State Secretary of the District Federal with protocol number 264/2007. Results: the themes of the study were found and classed in the following way: Pre-natal assistance, birth process and puerperal assistance. The women’s narrations were analyzed and it was referred in the major statements, humanization’s actions in the delivery moment and in the puerperal period, however the same women related scanty orientations and information in pre-natal appointments that would be very relevant to live these experiences with self-control and safety. Conclusion: the present study evidenced that at San Sebastian Birthing Center, the executed work correspond to a humanized assistance that is offered to the pregnant women who are admitted at this birthing center. The procedures that are used in this birthing center are humanized and they are according to World Health Organization’s recommendations, which were confirmed by the collected report of the women who participated of the study. Descriptors: birth; humanizing delivery; postpartum. RESUMO Objetivo: conhecer a percepção das puérperas sobre a assistência desenvolvida na Casa de Parto de São Sebastião do Distrito Federal. Metodologia: trata-se de estudo descritivo e exploratório, de abordagem qualitativa, com dez mulheres que vivenciaram o parto e puerpério na Casa de Parto após a aprovação do projeto de pesquisa pelo Comitê de Ética em Pesquisa da Secretaria de Estado em Saúde do Distrito Federal com parecer nº 264/2007. Resultados: as categorias temáticas encontradas foram: Assistência no pré-natal, Assistência no processo de parturição e Assistência no puerpério. Nas análises das falas das puérperas foi referido ações referentes à humanização da assistência no momento da parturição e puerpério, contudo as mesmas relataram escassez de orientações e informações no Pré-natal que julgaram ser importantes para vivenciar o parto e puerpério com segurança. Conclusão: o presente estudo evidenciou que o trabalho desenvolvido na instituição corresponde a uma assistência humanizada às parturientes que são acolhidas na Casa de Parto São Sebastião. Tais procedimentos utilizados estão em sintonia com as recomendações da Organização Mundial de saúde, o que foi constatado nos depoimentos colhidos das puérperas participantes do estudo. Descritores: parto; humanização no parto; puerpério. RESUMEN Objetivo: conocer la percepción de las puérperas acerca de la asistencia desenvuelta en la Casa de São Sebastião del Distrito Federal. Metodología:trata-se de uno estudio qualitativo con diez mujeres que tuvieran sus partos e puerpérios en la Casa Del Parto. Las categorías temáticas encontradas fueron: Asistencia durante la gestación, Asistencia en el proceso de parturición y Asistencia en el puerpério. El proyecto fue aprobado por el Comité de Ética de la da Secretaria de Estado em Saúde do Distrito Federal com parecer nº 264/2007. Resultados: en análisis a las respuestas de las puérperas, fue citado acciones acerca de la humanización de la asistencia durante la parturición y puerpério, entretanto las mismas relataron la escasez de orientaciones y informaciones en el prenatal que juzgaban importantes para la seguridad en el parto y puerperio. Conclusiones: el presente estudio evidencio que el trabajo desenvuleto en la instituición corresponde a una asistencia humanizada a las parturientes que son acollidas en la Casa del Parto. Los procedimientos utilizados estan en sintonia con las recomendaciones de la Organización Mundial de Salud, lo que fue constatado en los depoimientos collidos de las puérperas participantes del estudio. Descriptores: parto; humanización del parto; puerperio.